2019
DOI: 10.32677/ijch.2019.v06.i05.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of dengue fever and its clinical profile during an outbreak in a rural area in Tamil Nadu

Abstract: Background: In Southeast Asian countries, dengue is the major cause of pediatric morbidity and mortality and in that India reports the maximum number of cases. The annual incidence of dengue in India ranges from 8 to 33 million cases per year and an increased risk of dengue virus infection in children older than 5 years of age have been documented. Aim: The main objective of this study was to assess the incidence of dengue among the fever cases and to assess the clinical profile of various types of dengue feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Similar observations were made by Kumar et al [18]. Somasaundaram et al [14] noted that low hemoglobin, low platelet count were well associated with severe dengue but not total WBC and serum albumin.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar observations were made by Kumar et al [18]. Somasaundaram et al [14] noted that low hemoglobin, low platelet count were well associated with severe dengue but not total WBC and serum albumin.…”
Section: Discussionsupporting
confidence: 80%
“…Symptoms such as lethargy, vomiting, abdominal pain, epistaxis, edema, and altered sensorium were more commonly associated with severe dengue while headache, myalgia, upper respiratory symptoms, diarrhea, retro-orbital pain, and rash did not show much differences between both the groups and fever was common in both. Similar findings in severe dengue regarding fever, headache, vomiting, and oliguria were observed by by Somasundaram et al [14]. However, they also observed that diarrhea is more common in severe dengue but our study did not support that.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation